Bexarotene-induced hypothyroidism and dyslipidemia; a nation-wide study - Katsunori Manaka; Junichiro Sato; Yusuke Hikima; Hirofumi Horikoshi; Maho Taguchi; Akimichi Morita; Hiraku Suga; Hikari Boki; Taku Fujimura; Yoji Hirai; Takatoshi Shimauchi; Chiharu Tateishi; et al. (Endocrine Journal, 2024)
Central hypothyroidism and dyslipidemia are well-known adverse events (AEs) of bexarotene therapy. Although hypothyroidism is known to cause dyslipidemia, no study has examined the association between hypothyroidism and dyslipidemia in patients undergoing bexarotene therapy. The aim of this study is to examine this association. A retrospective observational study was performed among 294 patients who initiated bexarotene therapy in Japan (nation-wide postmarketing complete surveillance). Jonckheere-Terpstra (one sided) test was performed to evaluate the effect of the bexarotene dose on lipid metabolisms, and regression analyses were performed to evaluate associations of bexarotene dose, free thyroxine (FT4), body mass index (BMI), and lipid metabolisms. Most patients developed hypothyroidism. Two-third of patients showed FT4 values below the lower limit at 1 week. Triglycerides (TG) increased in a bexarotene dose–dependent manner, and grade ≥3 AEs on hypertriglyceridemia was observed in 39% of the patients. Additionally, one-third of grade ≥3 AEs on hypertriglyceridemia occurred within 1 week. The delta_FT4 (difference in FT4 from baseline) negatively correlated with TG increase at 1 week (p = 0.012) but not with low density lipoprotein cholesterol (LDL-C) increase at any week. Bexarotene-induced hypothyroidism is almost inevitable and occurred quickly. Bexarotene-induced hypertriglyceridemia showed positive bexarotene dose dependency and negative delta_FT4 dependency. Prophylactic and appropriate thyroid hormone compensation therapy and starting bexarotene at low doses with subsequent titration while managing dyslipidemia may have a beneficial effect for the successful continuation of bexarotene therapy without severe endocrine and metabolic AEs.